Coolidge ebook - Shlaes, Amity (2013)
Amity Shlaes, author of The Forgotten Man, delivers a brilliant and provocative reexamination of America's thirtieth president, Calvin Coolidge, and the decade of unparalleled growth that the nation enjoyed under his leadership. In this riveting biography, Shlaes traces Coolidge's improbable rise from a tiny town in New England to a youth so unpopular he was shut out of college fraternities at Amherst College up through Massachusetts politics. After a divisive period of government excess and corruption, Coolidge restored national trust in Washington and achieved what few other peacetime presidents have: He left office with a federal budget smaller than the one he inherited. A man of calm discipline, he lived by example, renting half of a two-family house for his entire political career rather than compromise his political work by taking on debt. Renowned as a throwback, Coolidge was in fact strikingly modern—an advocate of women's suffrage and a radio pioneer. At once a revision of man and economics, Coolidge gestures to the country we once were and reminds us of qualities we had forgotten and can use today.